Percutaneous Nephrolithotomy During Early Pregnancy in Urgent Situations: Is It Feasible and Safe? - Hosseini, Mohammad Mehdi; Hassanpour, Abbas; Eslahi, Ali; Malekmakan, Leila (Urology Journal, 2017)
Purpose: Urolithiasis during pregnancy poses risks for mother and the fetus with specific challenges in diagnosis and management. We report our experience with urgent percutaneous nephrolithotomy (PCNL) in seven pregnant patients with symptomatic renal stone in early pregnancy. Materials and methods: Seven pregnant patients with symptomatic renal stones were reviewed. The technique comprised PCNL with complete access under guide of ultrasonography in prone position under general anesthesia using pneumatic lithoclast for stone fragmentation. Results: There was no significant residual fragment of stone in the operated kidneys. The patients discharged without complications and delivered their babies healthy. Conclusion: PCNL should not be considered as the first therapeutic method in the first trimester of pregnancy, unless in urgent situations such as symptomatic renal pelvic stone with moderate to severe hydronephrosis in patients who do not tolerate or are complicated by nephrostomy or internal stent. However, this procedure could be technically demanding and should be done in centers with enough experience and equipment in percutaneous nephrolithotomy.